Pleasant places in the gospel according to John A classical motif as introit to theological awareness - King, Fergus J. 1962- (2017)
This piece notes that the locus amoenus motif, common in both Graeco-Roman literature and art, may have provided a literary entry point through which non-Judaic readers might have apprehended sections of the gospel according to John. An outline of the trope is followed by an exposition of passages which might be interpreted through this lens. The study reveals that use of the motif would provide an introit, but that many further layers of meaning were present to those who read the text from a Judaic background. This holds good for explorations of place in Samaria, the Temple and Galilee. In one important respect, the gospel shifts the way in which the motif works - by presenting Jesus as the focus and shaper of the desirable place, rather than the place itself simply as a metaphor or symbol of desirable elements.
Keywords: Christology; Temple; Gospel of John; locus amoenus; Symbolism